Relationship Between Diet and Nutritional Status with Blood Sugar Levels in Type 2 Diabetes Mellitus Outpatients at RSUD Ibnu Sina Gresik - Nabila Dwi Sabita; Inne Soesanti; Nuning Marina Pengge; Mujayanto; Siti Zaharah Rosli (Politeknik Kesehatan Kemenkes Surabaya, 2024)
Type 2 Diabetes Mellitus is a chronic disease with an increasing incidence in Indonesia and is closely related to blood sugar control. This study was conducted aimed to analyze the relationship between diet and nutritional status with blood sugar levels in outpatients with Type 2 Diabetes Mellitus at Ibnu Sina Gresik Hospital. A cross-sectional study design was employed along with observational analysis. The sample included 34 patients selected using the Accidental Sampling technique. Data were collected through interviews, questionnaires, measurements of height and weight, and laboratory results. The study was conducted from December 2023 to April 2024, and the data were analyzed using univariate and bivariate analysis using the chi-square test. The results showed that patients with poor diet and overweight tend to have abnormal blood sugar levels, with p=0.014 for diet and p=0.023 for weight gain, both significant (p<0.05). In conclusion, there is a relationship between diet and nutritional status and blood glucose levels in patients with Type 2 Diabetes Mellitus. It is recommended, patients should implement a diet according to the 3J principle, do sufficient physical activity, regularly monitor blood sugar levels, and make dietary changes such as reducing simple carbohydrates and sugar to manage blood sugar levels.